Age-specific Differences in Food and Stimulant Consumption in Germany and Their Marketing Implications. Issue 5 (20th October 2022) - Oeser, Gerald
Abstract: Elder food consumers have been a growing and attractive target group for the food industry for quite some time. Yet so far there have only been isolated, narrow comparisons of this target groups' food consumption to that of younger consumers. This paper provides an in-depth analysis of data gathered by the German Federal Statistical Office. It analyzes income and consumption sample data using multivariate analysis of variance to identify, in quantitative and monetary units, statistically significant differences in the food consumption of elder consumers compared to younger ones. At the same time, foods that are specifically consumed by these two age groups have been highlighted using discriminant analysis. Managerial implications have then been derived for food producers, marketers and retailers to reach the age groups under review more effectively and more efficiently. With Germany's second-largest and third-oldest population in Europe, its largest food and drinks market in the European Union and the most competitive European food retail sector, the results will also be relevant to international researchers and managers and will encourage further research in related fields.